Small-scale fisheries come into focus - Erickson, Sarah; Bevitt, Kate Melinda; Franz, Nicole (InfoFish International, 2023)
Findings from the forthcoming Illuminating Hidden Harvests (IHH) report show that small-scale fisheries produce 37 million tonnes of global catch and employ 90% of those working along the value chain in capture fisheries globally. These findings and others will add to the growing body of evidence around small-scale fisheries and support fisherfolk in achieving a ‘seat at the table’ in national, regional and global policy processes.